Government Must Not Territorialize the Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Huge Victory for Minority School Boards in Supreme Court B.C. School Board Case - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Townshippers’ Association Very Pleased with the Supreme Court of Canada’s Decision re: Minority Language Educational Rights - Townshippers' Association (2020)

FAQ Regarding the Canadian Emergency Response Benefit (CERB) Program - McSween, Pierre-Yves (2020)
Disclaimer: This document has been prepared with the information in public circulation as of March 26, 2020. This is not an official communication from the government and information presented here is not to be used as proof of eligibility. YES has translated and edited the original text for clarity. This information is provided solely as a resource. As this is an evolving document, the user of this information is responsible for determining and verifying the accuracy of the data presented here and how it is used.

How Powers are Divided Between our Federal and Provincial Governments - Quebec Community Groups Network (QCGN) (2020)